Singapore English, language mixing, and vernacular speech - Bolton, Kingsley (Routledge, 2022)
In this chapter, we present an overview of research on Singapore English, a field of academic inquiry which began in the mid-nineteen seventies, and which has expanded greatly throughout the following decades. Today, there is a small library of research on Singapore English, from multiple perspectives, not least with reference to the spread and features of the colloquial variety of the language known as ‘Singlish’. In our discussion of this topic, we have three broad aims: first, to describe the main tenets of the existing research tradition of Singapore English; second, to present the results of our own empirical research on the use of English by young people in Singapore; and, finally, to consider a number of key questions related to the notions of ‘Singapore English’ and ‘Singlish’. While our own research on English in the Singapore community may not be able to answer all these questions, we would at least hope that our findings might signpost useful opportunities for further research on such matters.